2014
DOI: 10.3904/kjim.2014.29.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Is propofol safe when administered to cirrhotic patients during sedative endoscopy?

Abstract: Background/AimsIn patients with liver cirrhosis, drugs acting on the central nervous system can lead to hepatic encephalopathy and the effects may be prolonged. Recently, misuse of propofol has been reported and the associated risk of death have become an issue. Propofol is commonly used during sedative endoscopy; therefore, its safety in high-risk groups must be further investigated. We performed a pilot study of the safety and efficacy of propofol during endoscopy in Korean patients with cirrhosis.MethodsUpp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…This finding is consistent with the results of previous studies that found that the risk of HEP was minimal with propofol-based sedation. 27,28 We believe that propofol-based sedation can be safely used for emergency endoscopy in patients with acute variceal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the results of previous studies that found that the risk of HEP was minimal with propofol-based sedation. 27,28 We believe that propofol-based sedation can be safely used for emergency endoscopy in patients with acute variceal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of liver cirrhosis on the effects of sedatives in cirrhotic patients remains unclear. A pilot study evaluated the safety and efficacy of propofol use during endoscopy in Korean patients with cirrhosis, and determined that sedation with propofol was well tolerated in cirrhotic patients; specifically, no deterioration in psychomotor function, even in cirrhotic patients with hepatic encephalopathy, was observed [ 28 ]. Our study is the first meta-analysis to evaluate anesthesia for UGIE in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since sensitivity to the sedative and cardiorespiratory depressant effects of propofol are increased in these patients, it is recommended to decrease the dose. Nevertheless, in a study of 20 patients with liver cirrhosis and 20 control subjects undergoing upper GI endoscopy, Suh et al [7] did not observe respiratory depression or clinically significant hypotension. Although psychomotor performance was more impaired in cirrhotic patients, there was no post-procedural deterioration of psychomotor function even in cirrhotic patients with minimal hepatic encephalopathy.…”
mentioning
confidence: 93%